Performance of Hybrid kenaf - bagasse particle boards compared with Commercial Board - Hassan Fwaz, Solafa Elsir; Elarabi, Salaheldin M.; Eltayeb, Musa; Osman, Zeinab (Gezira Journal of Engineering and Applied Sciences; Vol 17 No 2 (2022), 2026)
The pursuit of sustainable construction materials requires exploring bio-composites as alternative for conventional particle board used in green buildings. This study evaluate the mechanical properties of  bio-composite  panels made from a mixture of ( kenaf  fibers : bagasse fibers) with  urea-formaldehyde (UF) resin  as sustainable alternative to conventional particleboard.  Two types of panels were analyzed: a standard (Specimen S)  and specimen(B) (kenaf  fibers: bagasse fibers) (50:50). Key properties assessed included tensile strength, stress, strain, modulus of rupture (MOR), modulus of elasticity (MOE), Density, internal bond (IB) and young’s modules.  The specimen (B) exhibited Tensile Strengths of (21.6) MPA,as compared with the (Specimen S) which has the value of 23.4 MPA. The specimen (B) exhibited Stress of (20.1) MPA, as compared with the (Specimen S) which has the value of 22.3 MPA. The specimen (B) exhibited Strain of (0.84,) %, as compared with the (Specimen S) which has the value of 1.2%. The specimen (B) exhibited MOR of (20) MPA,as compared with the (Specimen S) which has the value of 21 MPA. The specimen (A) exhibited MOE of (1.8) GPA, as compared with the (Specimen S) which has the value of 2.6 GPA. The specimen (B) exhibited Density of (0.48) g/cm 3 as compared with the (Specimen S) which has the value of 0.6 g/cm 3 . The specimen (B) exhibited IB of (0.63) MPA, as compared with the (Specimen S) which has the value of 0.9 MPA. The specimen (B) exhibited young’s modules of (2280) MPA, as compared with the (Specimen S) which has the value of 2500 MPA. This study concludes that the Also the specimen B is shown mechanical properties which are relatively close to the standard (specimen S). The tensile strength, MOR, MOE, Young′s Modulus and strain were very good and the stiffness was good , but it showed lower flexibility and a slight decrease in internal bonding. It can be concluded according to the findings of this study that (specimen B ) can be used for interior panels (non –load bearing uses) and furniture in green buildings.The study recommended using additional proportions of kenaf fibers, improving the mechanical properties of specimens by increasing the fibers proportions, increasing the resin content and by applying higher mold pressure and increasing density enhances the MOR, MOE and IB values and makes specimens more suitable for industrial applications and green buildings construction. إن السعي نحو مواد بناء مستدامة قد أدي الي إستكشاف المواد المركبة الحيوية كبدائل للألواح الحبيبية التقليدية المستخدمة في المباني الخضراء. تهدف هذه الدراسة الي تقييم الخصائص الميكانيكية للألواح المركبة   الحيوية   المصنعة   من مزيج الياف الكناف: الياف البجاس، والمترابطة   باستخدام راتنج اليوريا فورمالدهيد. وتهدف الدراسة الي تقييم إمكانيات هذه الالواح   كبديل مستدام للألواح الحبيبية التقليدية. تم تحليل نوعين من الالواح المركبة: العينات القياسية والعينة (B) المصنوعة من الياف الكناف والبجاس بنسبة (50:50).                                                                                                    وشملت    الخصائص الرئيسة التي تقييمها: مقاومة الشد، والاجهاد، والانفعال، ومعامل الكسر، ومعامل المرونة، والكثافة، وقوة الترابط الداخلي ومعامل يونج. أظهرت العينة (B)مقاومة شد بلغت 21.6 ميجا باسكال بالمقارنة مع العينة القياسية التي تبلغ قيمتها 22.3ميجا باسكال . كما أظهرت العينة (B) اجهاداَ مقداره 20.1 ميجا باسكال. في حين بلغت قيمة الاجهاد للعينة القياسية 22.3   ميجا باسكال. كذلك سجلت العينة (B) انفعالاَ قدره 0.84 % مقارنة مع العينة القياسية التي سجلت 1.2 %. بالإضافة   الي ذلك، حققت   العينة (B) معامل كسر بلغ 20 ميجا باسكال، بينما سجلت العينة القياسية قيمة 21 ميجا باسكال. أظهرت   العينة   B)) أيضا معامل مرونة بلغ 1.8   جيجا باسكال، مقارنة بالعينة القياسية التي سجلت قيمة قدرها 2.6 جيجا باسكال. كما سجلت كثافة مقدارها   0.48 جرام /سم 3 في حين بلغت كثافة العينة القياسية نحو 0.6 جرام /سم 3 .وعلاوة علي ذلك   أظهرت العينة ((Bصلابة وكثافة اقل من العينة القياسية، مما يشير الي ان خصائص العينة القياسية كانت أفضل نسبيا من حيث    الأداء الانشائي. علاوة على ذلك، أظهرت العينة (B) قوة ترابط داخلي بلغت 0.63 ميجا باسكال، مقارنة بالعينة القياسية التي سجلت قيمة قدرها 0.90 ميجا باسكال. كما أظهرت معامل يونج بقيمة 2280 ميجا باسكال مقارنة بالعينة القياسية التي سجلت قيمة 2500 ميجا باسكال. خلصت هذه الدراسة الي ان العينة (B)  أظهرت خواص ميكانيكية قريبة جدا من العينة القياسية. فقد كانت قيم مقاومة الشد، ومقاومة الانحناء، ومعامل المرونة، ومعامل يونغ، والانفعال جيدة جدا، كما كانت الصلابة جيدة. ومع ذلك أظهرت العينة مرونة اقل وانخفاضاَ طفيفا َفي قوة الترابط الداخلي. واستناداِ الي نتائج هذه الدراسة، يمكن الاستنتاج ان العينة (B) يمكن استخدامها في تصنيع الالواح الداخلية والاثاث المخصص للمباني الخضراء.